(untitled) (Trabalho & Educação, 2017)
This article is part of the master’s research that sought to apprehend what is education in prisons through the social representations of educators in this environment. For this work the cut occurred in the aspect of the formation of this educator. Through the theoretical and methodological reference of the Social Representations, it was possible to approach the ways of thinking, feeling and acting of the subjects of the research on the education in prisons. When thinking about the formation process as dimensions of the teaching work, the concept of work was used in the Marxist perspective. In this sense, we intend to make some considerations about the specific and continuous training directed at these educators, as well as the production of knowledge in their practices. It was noticed that the subject of prison education is still little worked in the initial and continuous formation of teachers, which brings to the fore the need to think about projects and public policies of formation for educators in the prison context, since, the Lack of a more systematic attention, are in the challenge of constructing an educational practice contextualized with this environment and with the specificities of the students there. On the other hand, starting from the presupposition of work as an educational principle, it is known that there is construction of knowledge through their actions, in their own experience. ___ Este artigo é parte da pesquisa de mestrado que buscou apreender o que é a educação em prisões por meio das representações sociais dos educadores que nesse ambiente atuam. Para esse trabalho, o recorte se deu no aspecto da formação desse educador. Por meio do referencial teórico-metodológico das Representações Sociais, foi possível se aproximar das formas de pensar, sentir e agir dos sujeitos da pesquisa sobre a educação em prisões. Ao se pensar no processo de formação como dimensões do trabalho docente, utilizou-se o conceito de trabalho na perspectiva marxista. Nesse sentido pretendeu-se tecer algumas considerações acerca da formação específica e continuada voltada a esses educadores, bem como da produção de conhecimento em suas práticas. Percebeu-se que o tema da educação em prisões ainda é pouco trabalhado na formação inicial e continuada de professores, o que traz à tona a necessidade de pensar projetos e políticas públicas de formação para os educadores no contexto carcerário, uma vez que, por falta de uma atenção mais sistemática, encontram-se no desafio de construção de uma prática educativa contextualizada com esse ambiente e com as especificidades dos alunos ali reclusos. Em contrapartida, partindo do pressuposto do trabalho como princípio educativo, sabe-se que há construção de saberes através de suas atuações, na própria experiência.